Failure in international new ventures : the internationalization failure of software firms - Varrela, Lauri (My University, 2020)
The role of small software firms as drivers of innovation, economic growth, and employment has been growing in recent decades, especially as larger firms have been trending towards outsourcing and downsizing non-core activities. The Finnish software industry has similarly changed, with growth now being increasingly driven by large numbers of small firms instead of a small number of large companies as in the past. The growth and survival of many of these firms is contingent on reaching wider audiences than the Finnish market can provide which drives them to internationalize early and rapidly. The failure to internationalize can have significant impacts on the growth and long term survival of these firms and subsequently also impact the national economies which increasingly rely on these firms as employers and drivers of economic activity. This thesis set out to examine why international new ventures to fail in their internationalization by examining the antecedents, speed and extent, and outcomes of failure. To allow for a sufficiently in-depth examination of the phenomenon a qualitative research approach was chosen. The empirical data for this thesis was collected through theme-interviews with managers of software firms which had experienced internationalization failure. The findings of the empirical research were generally in line with literature and theoretical framework of this thesis. Findings suggest that the main motives for internationalization are connected to growth as the small size of the Finnish market limited the sales and recruitment opportunities of the firms. The antecedents of internationalization failure were found to be mainly internal, as the internationalization efforts of the firms suffered from poor planning and a lack of relevant market knowledge. The lack of existing networks in target markets seemed to also contribute to the difficulties that firms experienced in achieving sales and growth in new markets. The effects of external antecedents were limited as market conditions were generally stable during the events. Internationalization failure seemed to stem from factors early in the process and was relatively fast in most cases. The outcomes of failure were in most cases a withdrawal from the international market the firm was targeting. All firms in this study survived the internationalization failure they underwent and would have seemed to experience learning as a result, as many went on to successfully internationalize later. The failure seemed to have made firms more careful in their internationalization as most would subsequently internationalize more gradually after a stable customer base had been established in the market. Based on the findings of this thesis, internationalizing ventures would benefit from thorough market research and a more gradual approach to new markets which allow for the establishment of networks